Clinical and functional analyses of the novel STAR c.558C>A in a patient with classic lipoid congenital adrenal hyperplasia - Liu, Jie; Dai, Hong-Mei; Guang, Gao-Peng; Hu, Wen-Mu; Jin, Ping (Frontiers in Genetics, 2023)
Objective: Congenital lipid adrenal hyperplasia (LCAH) is the most serious type of congenital adrenal hyperplasia and is caused by steroid-based acute regulatory (STAR) protein mutations. Herein, we report compound heterozygous mutations c.558C>A (p.S186 R) and c.772C>T (p.Q258*) in a newborn 46 XY patient diagnosed with classic LCAH and explore their clinical and functional characteristics. Methods: Peripheral blood samples were collected from LCAH patient and their families. The pathogenic variant identified by whole-exome sequencing was further confirmed by Sanger sequencing and pedigree verification. The functional consequence and ability to convert cholesterol into progesterone of the identified STAR Q258* and S186 R mutations were analyzed by cell transfection and in vitro assays. Results: The proband was presented with severe glucocorticoid and mineralocorticoid deficiency, high adrenocorticotropic hormone, and enlarged adrenals. Heterozygous mutations p. S186 R and p. Q258* in the STAR gene were identified in the patient, and her parents were carriers, which is consistent with an autosomal recessive disorder. The STAR p. Q258* mutation has been reported and generates a truncated protein. The p. S186 R mutation is a novel variant that disrupts STAR. The residual STAR activities of p. S186R, p. Q258*, and p. S186R/p.Q258* were 13.9%, 7.3%, and 11.2%, respectively, of the wild-type, proving the main negative effects of the mutant proteins. Conclusion: Our findings reveal the molecular mechanisms underlying LCAH pathogenesis, further expanding the genotype and clinical spectrum of LCAH.